Photoelectron spin-polarization control in the topological insulator Bi 2Se 3 - Zhu, Zheng H.; Veenstra, C. N.; Haverkort, Maurits W. (Physical review letters, 2014)
We study the manipulation of the spin polarization of photoemitted electrons in Bi2Se3 by spin- and angle-resolved photoemission spectroscopy. General rules are established that enable controlling the photoelectron spin-polarization. We demonstrate the ± 100% reversal of a single component of the measured spin-polarization vector upon the rotation of light polarization, as well as full three-dimensional manipulation by varying experimental configuration and photon energy. While a material-specific density-functional theory analysis is needed for the quantitative description, a minimal yet fully generalized two-atomic-layer model qualitatively accounts for the spin response based on the interplay of optical selection rules, photoelectron interference, and topological surface-state complex structure. It follows that photoelectron spin-polarization control is generically achievable in systems with a layer-dependent, entangled spin-orbital texture.